Systematics of the rare Amazonian genus Eutrachelophis (Serpentes: Dipsadidae), with an emended diagnosis for Eutrachelophis papilio - Werneck, Fernanda de Pinho; Fernandes, Igor Yuri; Fraga, Rafael de; Entiauspe Neto, Omar Machado; Moraes, Leandro J.C.L. (Zoologischer Anzeiger, 2021)
Integrative analyses of multiple data sources and increased coverage in genetic and taxa sampling have been increasingly clarified the phylogenetic relationships of caenophidian snakes. However, some knowledge gaps remain, especially at higher-levels and among genera, and unclear relationships of some taxa with scant available information. One of these taxa is the recently described Amazonian genus Eutrachelophis (Dipsadidae), whose members are rarely recorded and lack associated molecular information. By analyzing recently collected specimens from Amazonian expeditions, we found a series of Eutrachelophis papilio and obtained molecular information (two mitochondrial genes and one nuclear gene) for two specimens. This allowed the first assessment of the molecular phylogenetic relationships of the genus Eutrachelophis. Molecular phylogenetic trees of the caenophidian diversification were inferred considering the information of 10 genes (five mitochondrial and five nuclear), under both Bayesian and Maximum Likelihood optimality criteria. Resulting trees corroborate the distinctiveness and taxonomic validity of Eutrachelophis, and its family and subfamily level allocation. A highly supported clade composed of Eutrachelophis and another enigmatic Amazonian genus, Arcanumophis, was recovered nested in the subfamily Xenodontinae. The Eutrachelophis + Arcanumophis clade is recovered as sister to a clade containing the remaining genera of tribe Xenodontini. These results do not corroborate that the phenotypic apomorphies of Eutrachelophis are secondarily developed within Xenodontini diversification, therefore refuting the recent allocation of this genus in this tribe. In the light of these results, we reassessed the morphological similarities of Eutrachelophis, Baliodryas and Arcanumophis and their distinctiveness among xenodontines. Based on combined phenotypic and molecular evidence, we propose the revalidation of tribe Eutrachelophiini to better reflect the high evolutionary distinctiveness of these snakes. We also obtained novel data on the morphometrics, meristics, color variations, natural history and geographical distributions from the analyzed museum specimens of Eutrachelophis papilio. We found a considerable variation in the range of analyzed morphological characters, including in some considered as diagnostic, justifying the designation of an emended diagnosis for the species. Despite these advances, some gaps remain with respect to these snakes, such as the taxonomic validity of Eutrachelophis species, molecular phylogenetic relationships of Baliodryas, and the internal and hemipenial morphology of Arcanumophis. Further investigation on these issues and reassessment of museum specimens should increase the knowledge associated with these rare snakes. © 2021 Elsevier GmbH
Keywords: Biological collection; Eutrachelophiini